Frequency and Type of Situational Awareness Errors Contributing to Death and Brain Damage: A Closed Claims Analysis. (August 2017) - Schulz, Christian M.; Burden, Amanda; Posner, Karen L.; Mincer, Shawn L.; Steadman, Randolph; Wagner, Klaus J.; Domino, Karen B.
Abstract : Background: Situational awareness errors may play an important role in the genesis of patient harm. The authors examined closed anesthesia malpractice claims for death or brain damage to determine the frequency and type of situational awareness errors. Methods: Surgical and procedural anesthesia death and brain damage claims in the Anesthesia Closed Claims Project database were analyzed. Situational awareness error was defined as failure to perceive relevant clinical information, failure to comprehend the meaning of available information, or failure to project, anticipate, or plan. Patient and case characteristics, primary damaging events, and anesthesia payments in claims with situational awareness errors were compared to other death and brain damage claims from 2002 to 2013. Results: Anesthesiologist situational awareness errors contributed to death or brain damage in 198 of 266 claims (74%). Respiratory system damaging events were more common in claims with situational awareness errors (56%) than other claims (21%, P < 0.001). The most common specific respiratory events in error claims were inadequate oxygenation or ventilation (24%), difficult intubation (11%), and aspiration (10%). Payments were made in 85% of situational awareness error claims compared to 46% in other claims ( P = 0.001), with no significant difference in payment size. Among 198 claims with anesthesia situational awareness error, perception errors were most common (42%), whereas comprehension errors (29%) and projection errors (29%) were relatively less common. Conclusions: Situational awareness error definitions were operationalized for reliable application to real-world anesthesia cases. Situational awareness errors may have contributed to catastrophic outcomes in three quarters of recent anesthesia malpractice claims. Situational awareness errors resulting in death or brain damage remain prevalent causes of malpractice claims in the 21st century. Abstract : Situational awareness errors resulting in death or brain damage remain prevalent causes of malpractice claims in the 21st century.